Research Trends On Reading The Yellow Book Using The Al-Miftah Lil Ulum Method : A Bibliometric Study - M. Rifqi Almahmudi; Abdur Rofik (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
The yellow book learning method has a fundamental role in the Islamic boarding school education system in Indonesia because it is the main means of mastering the treasures of classical Islamic science. One of the methods that is famously used is the Al-Miftah Lil Ulum Method from Sidogiri Islamic boadhing school, which is present as a learning innovation that offers a systematic approach in improving the ability to read classical Arabic texts without harakat. This study aims to analyze the development of scientific studies related to the Al-Miftah Lil Ulum Method using a bibliometric analysis approach. Data were collected from Google Scholar and Garuda databases through the keywords